To write the given quadratic equation to its vertex form, we first form a perfect square.
x² - 2x + 5 = 0
Transpose the constant to other side of the equation,
x² - 2x = -5
Complete the square in the left side of the equation,
x² - 2x + (-2/1(2))² = -5 + (-2/1(2))²
Performed the operation,
x² - 2x + 1 = -5 + 1
Factor the left side of the equation,
(x - 1)² = -4
Thus, the vertex form of the equation is,
<em> (x-1)² + 4 = 0</em>
7 to 9 I believe if you take 4 and 7 and make them more it schools be that
Answer:
3¹²
Step-by-step explanation:
Answer:
D |-11 | >-25
Step-by-step explanation:
|-11 | = 11
11 > -25